THE INFLUENCE OF TRAINING AND JOB PLACEMENT ON REGIONAL REVENUE AGENCY EMPLOYEE PERFORMANCE IN EAST KUTAI DISTRICT - Yuli Prastiani; Joko Sabtohadi; Praja Hadi Saputra (Jurnal Scientia, 2023)
There are findings, based on the data submitted with a total number of employees of 176, only 31 employees carry out training in the 2020-2022 period. Based on Anjab ABK data, the placement of employees does not match the existing qualifications. Training and job placement are factors that need to be considered because they are related to improving employee performance. This study intends to analyze the effect of training on employee performance, work placement on employee performance, the effect of training and job placement on employees, and the variables that most influence employee performance at the Bapenda office of East Kutai Regency. The sample used was 64 respondents. This research is a survey research using a quantitative approach. Data analysis in this study used multiple linear regression. The results in this study show that partially the training variable does not affect performance and the job placement variable has a significant effect on employee performance, simultaneously it has a significant effect on the performance of Bapenda employees in East Kutai Regency.